Beyond the Literary Sources of Augurello’s Chrysopoeia - Soranzo, Matteo (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2022)
In his Neo-Latin poem Chrysopoeia (1515), the Italian humanist Giovanni Aurelio Augurello often declares to be outdoing the ancients in writing the first alchemical poem in Latin. Is this simply an instance of what E. R. Curtius called outdoing a topos? Or is Augurello’s poem actually venturing onto a metaphorically untrodden path? Based on an analysis of Chrysopoeia, its genesis, and its sources, this article aims to assess the extent of this poem’s novelty. In particular, my interpretation focuses on this text’s poetic transpositions of non-literary sources, and more specifically Geber’s Summa perfectionis and other medieval alchemical texts.